2008
DOI: 10.1128/iai.00645-08
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2Produced byEntamoeba histolyticaBinds to EP4 Receptors and Stimulates Interleukin-8 Production in Human Colonic Cells

Abstract: Entamoeba histolytica pathogenesis in the colon occurs in a stepwise fashion. It begins with colonization of the mucin layer, which is followed by stimulation of a proinflammatory response that causes nonspecific tissue damage that may facilitate parasite invasion of the underlying colonic mucosa. Unfortunately, the parasite and/or host factors that stimulate a proinflammatory response in the gut are poorly understood. In this study, we found that live E. histolytica or secretory or proteins (SP) and soluble a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…On other hand, LTB 4 down-regulate IL-12, and up-regulate IL-10 by dendritic cells leading to immune tolerance [48]. These results also correlated well with the earlier reports conducted in experimental animals whereby Increase in LTB 4 in intestine has been demonstrated in other nematode-infected animals [49] [50] and other protozoan parasite as Entamoeba histolytica [51]. Experimental studies conducted on Strongyloides venezuelensis indicated greater LTB 4 release in the lungs, duodena and serum than that seen in the tissue of uninfected animals.…”
Section: Discussionsupporting
confidence: 88%
“…On other hand, LTB 4 down-regulate IL-12, and up-regulate IL-10 by dendritic cells leading to immune tolerance [48]. These results also correlated well with the earlier reports conducted in experimental animals whereby Increase in LTB 4 in intestine has been demonstrated in other nematode-infected animals [49] [50] and other protozoan parasite as Entamoeba histolytica [51]. Experimental studies conducted on Strongyloides venezuelensis indicated greater LTB 4 release in the lungs, duodena and serum than that seen in the tissue of uninfected animals.…”
Section: Discussionsupporting
confidence: 88%
“…These data suggest that PGE 2 coupling through EP4 and EP2 receptors can therefore act in an opposing manner to either promote (EP4) or decrease (EP2) IL-8 expression, even though both receptors use the same second messenger, cAMP. Since Chadee's laboratory has reported that PGE 2 promotes IL-8 production in the human colonic epithelial cell lines Caco-2 and T84 through both the PKA and PI3K pathways (Dey and Chadee, 2008;Dey et al, 2009;Srivastava et al, 2012), it appears that EP4 contributes to IL-8 production.…”
Section: Other Immune Cellsmentioning
confidence: 99%
“…COX inhibitors were removed by centrifugation, followed by 2 hours of incubation in fresh HBSS for collecting SP as described previously. 18 In another experiment, 100 mol/L AA was added to trophozoites in HBSS at the start of the 2-hour incubation and SP was collected.…”
Section: Sps Of E Histolyticamentioning
confidence: 99%
“…We have recently shown that E. histolytica PGE 2 signals via the host epithelial EP4 receptors to induce robust IL-8 secretion that could augment inflammation. 18 Because PGE 2 is strongly associated with various diarrheal diseases, however, we reasoned that ameba-derived PGE 2 might play a major role in the onset of diarrhea during acute amebic colitis.…”
mentioning
confidence: 99%